Elite collective agency and the state - Korkut A. Ertürk (The University of Utah, Department of Economics, 2019)
The paper explores how elites can develop capacity for collective agency through coordination. Elites' challenge is to simultaneously deter the state from abusing power while at the same time relying on it to discipline defectors in their midst. The basic insight holds that the credibility of the state's threats depends on the cost of carrying them out, which elites can have control over if they can act in tandem. Elites can coordinate in being compliant when the ruler's threats serve their collective interest which raises the threats' credibility, while lowering that of those they dislike by their coordinated noncompliance making them costly to carry out.
Keywords: C72; D72; D02; 330; elite collective agency; state power; coordination; credible threats; subgame imperfect equilibrium